2020
DOI: 10.3390/en13010207
|View full text |Cite
|
Sign up to set email alerts
|

Internal Flow Analysis of a Heat Transfer Enhanced Tube with a Segmented Twisted Tape Insert

Abstract: A heat exchanger is a device that transfers unneeded heat from one region to another, and transferred heat may be fully reused, thus improving energy efficiency. To augment this positive process, many studies and investigations on automation technologies have been performed. Inserts are widely used in pipe flow for heat transfer enhancement, since they can break the boundary layer and promote the heat exchange. Segmented twisted tape, which is applicable in 3D printing, is a novel insert and has potential in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In the other recent investigation of Liu et al, [16] indicates that the geometric parameters like twist ratio and length ratio play an important role in heat transfer enhancement. The results showed that a segmented tape insert in pipe flow can increase the overall heat transfer rate by 23.5% and the friction factor by 235%, while local improvement along the tube can be 2.8 times more than the plain tube [16]. Figure 8 illustrates the relationships between heat transfer coefficient and twist ratio along the tube.…”
Section: A B Cmentioning
confidence: 88%
See 2 more Smart Citations
“…In the other recent investigation of Liu et al, [16] indicates that the geometric parameters like twist ratio and length ratio play an important role in heat transfer enhancement. The results showed that a segmented tape insert in pipe flow can increase the overall heat transfer rate by 23.5% and the friction factor by 235%, while local improvement along the tube can be 2.8 times more than the plain tube [16]. Figure 8 illustrates the relationships between heat transfer coefficient and twist ratio along the tube.…”
Section: A B Cmentioning
confidence: 88%
“…(3) The tube having T-W inserts with P/W of 1.18 produces the highest friction factor, which is 11.6 and 2.72 times greater than the plain tube. Segmented twisted tape Insert [16] Air (10000 ≤ Re ≤ 35000); Twist ratio = (2.0, 3.3 and 4.6); Length ratio = (0.3, 0.5 and 0.7)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) T b calculated as the average volumetric temperature of the whole channel. This method of calculation is most often used by most researchers, both for empty channels and those equipped with inserts or other turbulators, e.g., [22][23][24][25][26][27][28][29][30][31][32]. The heat flux is transferred to the fluid in contact with the channel wall, and its average temperature is a result of the heat transfer conditions and the medium's velocity on both sides of the insert.…”
Section: Pec Coefficientmentioning
confidence: 99%
“…An approach for increasing the thermal performance of a thermal system is to adopt a passive method, such as alteration of the fluid flow inside a tube including having a corrugated channel/tube or using insert inside the channel/tube [1,2]. Therefore, several modifications have been made to the twisted tape by researchers to produce better fluid mixing with lower ∆P including serrated twisted tape (TPP) [3], multiple twisted tape [4], square and V-cut twisted tape [5], segmented twisted tape [6], and self-rotating twisted tape [7]. Even though all these methods are able to enhance η at a certain point, a decreasing trend is shown as Re increases.…”
Section: Introductionmentioning
confidence: 99%